Morphological Diversity in Castor (Ricinus communis L.): A Metroglyph Analysis Approach to Reveal Hidden Patterns: Metroglyph Analysis in Castor (Ricinus communis L.) - Delvadiya, Indrajay; Ginoya, A. V.; Madariya, R. B.; Dobariya, K. L. (Annals of Arid Zone, 2024)
In this study, the performance of castor plants in arid zones or regions was thoroughly examined, emphasizing their suitability for such challenging environments. Castor is well-known for its resilience in arid conditions, making it an ideal crop for regions with limited water resources. An experiment was conducted to study the pattern of morphological variation for six characters in 22 elite castor inbred lines by Metroglyph and Index score method. Each genotype was represented by a closed circle, with the X-coordinate being seed yield per plant and the Y-coordinate being plant height. The remaining four characters were represented by rays of different positions on the glyph, with the length of the rays indicating the range. The line had a low value with no ray, medium value with a short ray, and a high value with a long ray. Scatter diagram revealed that maximum numbers of genotypes 7 were found in group IV. Metroglyph and Index score analysis revealed maximum variability for different characters in first and four group which comprised seven and four genotypes, respectively. The results unveiled seven distinct groups with unique morphological variations. The highest index score observed was 16 for genotypes RG-3041 while lowest score is 6 for JI-424. This study serves as a treasure map for breeders, offering promising trait combinations hidden within the gene pool, paving the way for remarkable advances in plant breeding and agricultural exploration.